Identification and spatio-temporal tracking of ubiquitous phage families in the human microbiome - Tadmor, Arbel D.; Mahmoudabadi, Gita; Foley, Helen B.; Phillips, Rob (Frontiers in Microbiomes, 2023)
Viruses are a major component of the human microbiome, yet their diversity, lifestyles, spatiotemporal dynamics, and functional impact are not well understood. Elucidating the ecology of human associated phages may have a major impact on human health due to the potential ability of phages to modulate the abundance and phenotype of commensal bacteria. Analyzing 690 Human Microbiome Project metagenomes from 103 subjects sampled across up to 18 habitats, we found that despite the great interpersonal diversity observed among human viromes, humans harbor distinct phage families characterized by their shared conserved hallmark genes known as large terminase subunit (TerL) genes. Phylogenetic analysis of these phage families revealed that different habitats in the oral cavity and gut have unique phage community structures. Over a ~7-month timescale most of these phage families persisted in the oral cavity and gut, however, presence in certain oral habitats appeared to be transitory, possibly due to host migration within the oral cavity. Interestingly, certain phage families were found to be highly correlated with pathogenic, carriage and disease-related isolates, and may potentially serve as novel biomarkers for disease. Our findings shed new light on the core human virome and offer a metagenomic-independent way to probe the core virome using widely shared conserved phage markers.